РОЗУМІННЯ ГУМАНІЗМУ НА СУЧАСНОМУ ЕТАПІ РОЗВИТКУ УКРАЇНСЬКОЇ ДЕРЖАВИ (Педагогіка вищої та середньої школи, 2009)
The article considers new approaches to understanding humanism. Three leading tendencies of realization of educational influence on the person are opened